Fascin Expression as Prognostic Factor for Survival in Advanced Epithelial Ovarian Carcinoma - Vitantri, Fara; Purbadi, Sigit; Siregar, Budiningsih; Sutrisna, Bambang (Indonesian Journal of Obstetrics and Gynecology, 2015)
Objective: To evaluate fascin expression as a prognostic factor and its correlation with survival and clinicopathologic factors (degree of differentiation and stage) in epithelial ovarian carcinoma. Methods: This study is prognostic study with historical cohort design. Fascin was analyzed in paraffin block sections of 33 advanced stage ovarian carcinoma patients using immunohistochemistry. Fascin expression was tested for its correlation with overall survival as well as with grade and stage of the cancer. Results: In this study, fascin expression has no correlation with survival. In the period of 17-22 months, samples with high fascin expression had a HR of 1.59 (95% CI=0.38-6.67, p=0.449), but in the period of 17-23 months, both groups had comparable HR. In the period of more than 23 months, samples with high expression of fascin had a better HR of 0.40 (95% CI=0.04-4.38, p=0.449). No significant correlation was found between fascin expression with grade (OR=2.08, 95% CI=0.44-9.84, p=0.442) and stage (OR=2.70, 95% CI=0.39-18.96, p=0.360). Conclusion: In this study, there was no correlation between fascin expression and survival, and also no correlation between fascin, grade and stage. Further study with a larger, more homogenous sample, analyzing confounding factors is needed. [Indones J Obstet Gynecol 2015; 3-4: 222-229] Keywords: advanced stage ovarian carcinoma, fascin, survival